(untitled) (Global Journal of Human-Social Science, 2013)
This paper examines the contribution of the discipline in Africa It is argued that psychology has a significant role to play in solving educational social psychological health and other related problems affecting developing countries Due to problems of urbanization Modernization and westernization the need for adequately trained indigenous psychologists who can skillfully analyze and suggest solution has been underscored The use of proper methodological designs suitable to the African environment will have to be employed in order to avoid the pitfalls heretofore encountered by researchers in the interpretation of results arising from biased techniques The complexity and diversity of cultures in African countries should enrich the research base for psychological investigations which should in turn lead to wideranging solutions to the ensuring problem The challenge and role of psychology to development in Africa cannot therefore be gainsaid